INTERNATIONAL AND BRAZILIAN FAIR TRADE: A COMPARATIVE SOCIOLOGICAL ANALYSIS OF MARKET MODELS AND RATIONALITIES - Daniel Alves Carvalho, Antonio (Revista Gênero e Interdisciplinaridade, 2026)
The article presents a sociological comparative analysis between the international fair trade model (WFTO/Fairtrade International) and the Brazilian fair and solidarity trade model (SNCJS), which is linked to the solidarity economy and public policies. Based on Karl Polanyi and the notion of the (re)embeddedness of the economy, it interprets fair trade as a countermovement against deregulated commodification, seeking to reorient markets according to principles of social justice, sustainability and labour rights. Through qualitative documentary research (standards, decrees, reports and literature from 2004 to 2014), the study systematizes definitions, principles, target groups, certification mechanisms, participation criteria and actors’ views. It shows that the international model constitutes a private regime of ethical regulation of North–South global value chains, grounded in thirdparty certification and technicalcontractual criteria that tend to favour more structured organizations. The Brazilian model, in turn, configures a hybrid market, publicly and socially regulated, centred on Solidarity Economic Enterprises, public–social governance arrangements and guarantee mechanisms that combine audited certification, participatory systems and state declarations. It concludes that this hybridity broadens the substantive dimension of economic rationality, bringing fair trade closer to agendas of local development, socioproductive inclusion and the democratization of market relations.